A Thematic Integrated English Vocabulary Glossary for EYL - Intan Kurnia Awaliyani; Yudi Basuki (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2022)
The objective of this research is to develop A Thematic Integrated English Vocabulary Glossary for EYL In Trenggalek as a book/guideline for English language learning based on the 2013 curriculum of PAUD at PAUD level. This research uses R&D research design, a research design aimed at developing educational products, such as curriculum, syllabus, books, instructional media, etc. The B class student of BA Aisyiyah Suruh in 2018/2019 academic year consist of 12 students; 5 students of female and 7 students of male students. The researcher used questionnaire and interview as instrument of the research. The data obtained from questionnaires are analyzed quantitatively, while interview data is analyzed qualitatively. The products have been developed based on the needs of students, teachers, and parents, studying theory of R&D, studying theory of thematic learning, studying theory of vocabulary, studying theory of glossary and studying theory of EYL. The product has been developed through five steps of development. Based on the result of students' needs, its score was 78%, then student parents score was 774, and the result of teacher interviews showed that the teachers needed this product. It shows that all respondents agree that they need this product as a book/guideline in thematic English learning complying with the 2013 curriculum of PAUD. Meanwhile, the result of field testing the product of the students showed a percentage of 92%, 785 scores of students’ parents’ feedback, and positive responses to the teacher’s interviews. It indicates that the product of this research results is feasible to be used as a book/guideline for English language learning based on the 2013 curriculum of PAUD at PAUD level.